Gastroduodenal perforation: treatment and results - Camaño, Mario C; Castiglioni, Juan C; Cazabán, Luis A (Cirugía del Uruguay, 2021)
The author presents a series of 80 gastroduodenal perforations with a death rate of 18,75 %. With special reference to post-operatory complications. Death rate is very high in the female sex and in gastric cancer. Distant prognosis reveals that half of these patients in which a simplo dosure was performed, continued suffering; that one third needed a' second operation and that sixty percent of the patients were reoperated within the first year after perforation occurred.